PENGARUH KOMITMEN ORGANISASI DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Pada Kantor Kecamatan Rasanae Barat Kota Bima) - Khairul Amar; Meutia Meutia; Diswandi Diswandi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
This study aims to: (1) Test and analyze the effect of organizational commitment on employee performance at the Rasanae Barat Sub-District Office in Bima City (2) Test and analyze the effect of work involvement on employee performance in the Rasanae Barat Sub-District Office in Bima City. (3) Test and analyze the effect of organizational commitment on motivation at the Rasanae BaratSub-District Office in Bima City. (4) Test and analyze the effect of work involvement on motivation at the Rasanae BaratSub-District Office in Bima City. (5) Test and analyze the effect of motivation on employee performance at the Rasanae Barat Sub-District Office in Bima City. This research is a quantitative research. The population in this study were all employees working in the Rasanae Barat District Office in Bima City as many as 112 people. Determination of the sample by using the Slovin formula in order to obtain a sample of 88 people. Sampling method used was a simple random sampling technique and each employee has the same possibility to be selected as a sample. The instrument reliability test includes a validity test and a reliability test. The model that used in this research is a model of causality or relationship or influence and to test the proposed hypothesis, the analysis technique used was quantitative analysis with a path analysis approach. The results of the study show that (1) There is an influence of organizational commitment on employee performance at the Rasanae Barat Sub-District Office in Bima City with a significance value of 0.021 less than 0.05 (significant). (2) There is an influence of work involvement on employee performance at the Rasanae Barat Sub-District Office in Bima City with a significance value of 0.015 which is less than 0.05 (significant). (3) There is an influence of work organization commitment to motivation at the Rasanae Barat Sub-District Office in Bima City with a significance value of 0.004 which is less than 0.05 (significant). (4) There is no influence of work involvement on motivation in the Rasanae Barat Sub-DistrictOffice in Bima City with a significance value of 0.331 which is greater than 0.05 (not significant). (5) There is a motivational effect on employee performance at the Rasanae Barat Sub-District Office in Bima City with a significance value of 0.041 which is less than 0.05 (significant).